Roadmap to Consider Physiological and Psychological Aspects of User-product Interactions in Virtual Product Engineering - Wartzack, Sandro; Schröppel, Tina; Wolf, Alexander; Miehling, Jörg (Proceedings of the 22nd International Conference on Engineering Design (ICED19), 2019)
To successfully facilitate user-centred design, a multitude of different aspects has to be considered, from purely physiological to psychological-emotional factors. The overall aim is to increase the customer satisfaction by enhancing the fit between products and their users in the respective context of use. Further virtualisation of user-centred design processes holds the potential to convey the concepts of frontloading and predictive engineering from classical product engineering. Our vision is to facilitate a comprehensive consideration of user-product interactions in virtual product engineering operationalised by the mission to develop methods and tools to assess and design user-product interactions according to physiological and psychological aspects. A variety of work has already been done to model musculoskeletal user groups, to configure, predict, simulate and optimise physical user-product interactions, to integrate such models into CAD or to map individual subjective values to product design. Nevertheless, there are still research areas to be addressed to enable a comprehensive implementation of the mentioned approach. These are discussed in the present contribution
Keywords: User centred design; Simulation; Integrated product development; Affective Engineering; Biomechanical digital human models